Antimicrobial Effects of Metal Coatings or Physical, Chemical Modifications of Titanium Dental Implant Surfaces for Prevention of Peri-Implantitis: A Systematic Review of In Vivo Studies - Maria Gkioka; Xiaohui Rausch-Fan (MDPI AG, 2024)
Introduction: Peri-implantitis poses a significant challenge for implant dentistry due to its association with bacterial colonization on implant surfaces and the complexity of its management. This systematic review aims to assess evidence from in vivo studies regarding the antimicrobial efficacy of titanium (Ti) dental implant surfaces following physical/chemical modifications or the application of various metal element coatings in preventing bacterial growth associated with peri-implantitis. Materials and Methods: A literature review was conducted across four scientific databases (PubMed, Embase, Scopus, Web of Science), encompassing in vivo studies published between 2013 and 2024, and 18 reports were included in the systematic review. Results: The findings suggest that titanium dental implant surfaces, following physical/chemical modifications and metal element coatings, exhibit antimicrobial effects against bacteria associated with peri-implantitis in humans and various animal models. Conclusions: The reviewed studies indicated a reduction in bacterial colonization, diminished biofilm formation, and decreased signs of inflammation in the peri-implant tissues, which provides evidence that physical/chemical alterations on titanium dental implant surfaces or metal element coatings, like silver (Ag), zinc (Zn), magnesium (Mg), and copper (Cu), demonstrate antimicrobial properties in in vivo studies. However, caution is warranted when translating findings to clinical practice due to methodological disparities and high bias risks. Further larger-scale clinical trials are imperative to assess their long-term efficacy and validate their clinical applicability.